1989
DOI: 10.2466/pms.1989.68.3.807
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychology of Posttraumatic Stress Disorder: A Pilot Study

Abstract: The purpose of this paper was to describe a pilot neuropsychological investigation of Posttraumatic Stress Disorder. 14 patients diagnosed (by DSM-III-R criteria) as having posttraumatic stress disorder were administered the Four-word Short-term Memory test. Only two of the 14 patients did not meet one of the two criteria for cognitive impairment. Research directions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 4 publications
0
11
0
4
Order By: Relevance
“…Although short-term memory impairment may occur in some individuals with PTSD (Everly and Horton, 1989), reexperiencing phenomena suggest that trauma may enhance memory for aversive events. Freud (1895) and Janet (van der Kolk, 1989), first to recognize that traumatic memories were distinct from ordinary memories, were followed by later theorists (Foa et al, (1989).…”
Section: Introductionmentioning
confidence: 99%
“…Although short-term memory impairment may occur in some individuals with PTSD (Everly and Horton, 1989), reexperiencing phenomena suggest that trauma may enhance memory for aversive events. Freud (1895) and Janet (van der Kolk, 1989), first to recognize that traumatic memories were distinct from ordinary memories, were followed by later theorists (Foa et al, (1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies included PTSD patients with significant psychiatric co-morbidity, so that the extent to which the observed deficits are specifically attributable to PTSD remains unclear. In studies of veterans diagnosed with PTSD, only mild to moderate neuropsychological deficits have been reported and several have not shown indications of higher cognitive impairments [Dalton et al, 1989;Everly and Horton, 1989;Gurvits et al, 1993], but other studies dealing specifically with combat-related PTSD have shown fairly specific deficits in the monitoring and regulation of memory information [Yehuda et al, 1995], as well as deficits in short term [Bremner et al, 1993] and long-term memory [Gilbertson et al, 1997[Gilbertson et al, , 2001Vasterling et al, 1998Vasterling et al, , 2002Yehuda et al, 2005]. Part of the discrepancies in these findings may be due to the use of different comparison groups.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD patients report deficits in declarative memory (remembering facts or lists, as reviewed below), fragmentation of memories (both autobiographical and trauma-related) and dissociative amnesia (gaps in memory that can occur for minutes to days and are not due to ordinary forgetting). On the basis of clinical reports and the tentative results of Everly and Horton (1989), Gil, Calev, Greenberg, Kugelmass, and Lerer (1990) hypothesised that there are memory deficits in PTSD patients. In their study, PTSD patients were male combat veterans and victims of terrorism or vehicle accidents who had abused alcohol or other substances, yet had been drugfree for at least two weeks.…”
Section: Discussionmentioning
confidence: 97%